THE EFFECT OF AUDIT TENURE, AUDIT FEES, AND FIRM SIZE ON AUDIT QUALITY - Alyasheza Putri Alifa; Edelweis Shevyvanya Ramdhan; Ade Imam Muslim (Universitas Tulungagung, 2025)
This study aims to examine the influence of audit tenure, audit fees, and firm size on audit quality. This study utilises yearly reports from 2022 and 2023 obtained from food and beverage companies registered on the Indonesia Stock Exchange (IDX). This study advances the existing literature by focussing on the food and beverage sector, which has been insufficiently explored in prior research. This study investigates the influence of these parameters on the likelihood of a firm engaging a high-quality auditor. The sample consists of 51 firms selected by purposive sampling. The quality of an audit is indicated by the classification of the public accounting firm, particularly its association with the Big Four. This study employs a quantitative methodology and performs logistic regression analysis to investigate the relationship between independent variables and audit quality. The outcomes of this study reveal that audit tenure and company size do not significantly influence audit quality, however audit fees exert a considerable effect on audit quality.